Ameriška geografija - Gosar, Anton (Geografski vestnik, 2024)
The American Geographical Society (AAG) celebrates in 2024 its 120th anniversary. The annual meetings of the AAG are popular among American geographers, recently they’ve become a stage of presenting professional research results by foreign, including Slovenian geographers. The aim of this paper is to identify the reasons for the growing popularity and to define the changed focus of the gatherings in the three decades of Slovenian presence. The article deals with the period of Slovenian independence. The study is based on available conference programs and paper titles or/and key words published. The contents and authors of Slovenian contributions are confirmed by the COBISS Co-operative Online Bibliographic System. In the first few decades of existence, AAG annual meetings were held at universities in the eastern part of North America; in this century AAG annual meetings are mainly hosted in large metropolis with adequate conference capacities. In the last two meetings more than 5000 papers were presented; compared to 1992, the number of papers presented have increased by three times. In the last three decades the focus of geographical research has changed to a certain extent. The presence of physical- and regional-geographical presentations decreased and issues in human geography – with urban geography at the forefront – as well as methods monitoring the geographic perception, especially GIS, have gained ground. During the considered period 47 papers were presented by Slovenian scholars; they dealt with political- and social-geographic issues, rural-urban relations and issues related to geographic education. Based on presentations at AAG meetings, the activities of Slovenian geographers have become known to American geographers and, on this foundation, several institutional partnerships, scholarships, excursions, research projects and guest lectureships by Slovenian geographers in the USA and by American colleagues in Slovenia have taken place.
Keywords: American Geographic Society; Ameriško geografsko društvo; geografska združenja; geografski kongresi; geographical associations; geographical congresses; history of geography; Slovene geography; slovenska geografija; United States of America; Združene države Amerike; zgodovina geografije